Industrial Policy of Bangladesh 2010-A Critical Evaluation - Rahman, Md. Mushfiqur (Asian Accounting and Auditing Advancement, 2012)
Reviewing the characteristics of the economy of Bangladesh and realizing the prospects of the industrial sector, it is our view that the promotion and expansion of the industrial sector is the most time-befitting task for the economic development of Bangladesh. Industrial policy should be formulated with a view to maintaining balanced regional growth through the setting up of prioritized industries. The main objective of the study is to find out the problems that lie in the present policy and suggest how to overcome those. Data have been collected mainly from secondary sources to conduct the study. This paper does not criticize all the aspects of the policy, only four important and controversial aspects of Industrial Policy, 2010 have critically been evaluated. These are private sector; small, cottage, micro, high-tech, and rural industries; women’s participation in industrialization, and priority determination for industrial development. Adequacy of various types of incentives offered in the policy for setting up prioritized industries as well as problems in maintaining coordination for policy formulation and monitoring activities for implementation of policy measures have been discussed and evaluated. This paper expresses the reasons for the failure of previous industrial policies in the pace of industrialization. This study also scrutinizes the problems that lie in the present policy and as such the pragmatic steps that should be taken for industrialization and incorporated into the industrial policy for achieving overall economic emancipation of the country. Accordingly, an endeavor has been made to suggest removing the structural impediments and policy obstacles in this paper. This study suggests and emphasizes preparing a policy for building a strong domestic industrial base i.e. local demand and need-based home industries and to way out for development and expansion of export-oriented and import-substitute industries and protecting them from outside competition.